Ball-milled graphene quantum dots for enhanced anti-cancer drug delivery - Prabhakar, Arun Kumar (2023)
Graphene quantum dots (GQDs) exhibit excellent opto-electronic properties along with fine-tunable structure and surface properties, which have made them versatile drug carriers. Here GQDs were prepared using carbon black as precursor through oxidation and ball-milling. The prepared GQDs were found to be nano-sized, oxidized, water-soluble and highly fluorescent. The GQDs were found to be extremely biocompatible against the tested cell lines namely: LO2, HeLa, PC-12 and MCF-7 and uptaken by cancer cells in greater amounts with increased concentrations and incubation times. B-Lapachone, an anti-cancer hydrophobic drug, was loaded onto the GQDs through pi-pi bonding and tested for its release profile through dialysis. The drug was released at a significantly higher rate at acidic pH specifically, to cancer cells as compared to the normal cell's relative alkaline pH. The GQD-drug conjugate was found to exhibit enhanced cytotoxicity in cancer cell lines relative to free drug from MTT assay. In whole, sized-down GQDs, having excellent biocompatibility and photostability with enhanced drug delivery properties has been designed and tested.